Pengaruh Metode Belajar dan Tingkat Penalaran Formal terhadap Hasil Belajar Fisika Siswa - Maria Dewati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
The purpose of this study was to determine the effect of the method of learning the physics student learning outcomes, to determine the effect of the level of formal reasoning students' physics student learning outcomes, and to determine the effect of the interaction methods of learning and level of formal reasoning. The method used is the method exsperimen. Samples were taken by 30 students to 15 students in the control class and 15 students of class exsperimen, and simple random technique. The data was collected by distributing directly to the sample test. Data analysis using descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics is to find the coefficients. The results showed: 1) a positive effect on learning outcomes approach to learning physics students with Fcount (43.199)> F table (4.02). 2) There was a positive influence on students' level of formal reasoning physics student learning outcomes Fcount (10.746)> TTable (4.02). 3). The interaction method of learning with students' level of formal reasoning with the Fcount (8694)> F table (4.02). 4) There is an average difference between the learning outcomes approach to learning (inquery and conventional) with t0 = 5.585 and sig = 0.000 <0.05. 5) There is an average difference between the levels of learning outcomes of formal reasoning (High and Low) with t0 = 2.291 and sig = 0.026 <0.05.